2010
DOI: 10.1111/j.1751-7176.2010.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Coronary Microvascular Function After Angiotensin Receptor Blocker Treatment With Irbesartan in Patients With Systemic Hypertension

Abstract: Patients with hypertension exhibit changes in vessel conductance and resistance. The aim of this study was to evaluate the effect of the angiotensin receptor blocker irbesartan on coronary microvascular function. Thirty‐six hypertensive patients without coronary artery or systemic disease were examined. Coronary flow velocity reserve (CFR) was measured using transthoracic Doppler echocardiography in 18 men (54±9 years) before and after 3 months of treatment with 600 mg/d of irbesartan and in 18 controls (55±11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…In contrast to the presented results, previous studies have shown that antihypertensive pharmacologic agents such as carvedilol (Xiaozhen et al, 2010) and angiotensin-receptor blockers (ARB) (Lethen et al, 2011) are associated with an increase in CFR in patients with hypertension. Different from the findings from the ARB-study conducted by Lethen et al (2011), RDN was not associated with significant changes regarding ABPM in the presented analysis. ABPM improves BP management by providing a comprehensive BP profile recorded in the patients 0 daily environment and correlates closely to the development of end-organ damage and the risk of cardiovascular events (Kikuya et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the presented results, previous studies have shown that antihypertensive pharmacologic agents such as carvedilol (Xiaozhen et al, 2010) and angiotensin-receptor blockers (ARB) (Lethen et al, 2011) are associated with an increase in CFR in patients with hypertension. Different from the findings from the ARB-study conducted by Lethen et al (2011), RDN was not associated with significant changes regarding ABPM in the presented analysis. ABPM improves BP management by providing a comprehensive BP profile recorded in the patients 0 daily environment and correlates closely to the development of end-organ damage and the risk of cardiovascular events (Kikuya et al, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Follow-up time was limited to 6 months, leaving potential changes in CFR beyond this observation period undetected. However, the effects of antihypertensive treatment on CFR within 6 months have been demonstrated in several previous studies (Xiaozhen et al, 2010;Lethen et al, 2011), which constituted the rationale for the selected observation period in the presented study. Finally, drug adherence was not assessed by any advanced means.…”
Section: Study Limitationsmentioning
confidence: 80%
“…Only 3 of the included studies were randomized and placebo‐controlled, 7 studies were randomized with an active or inactive comparator, and 10 studies were nonrandomized . A control group was included in a few studies, but only 2 nonrandomized studies performed a second measurement in the control group at the end of the study period.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Amelioration of both CFR and BP variability has been reported after 6 months of angiotensin receptor blocker treatment. 36 A third important potential explanation is the presence of inflammation and oxidative stress. Inflammation plays a role in the pathogenesis of atherosclerosis, and it has been reported to be associated with coronary microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%